2002
DOI: 10.1097/00000539-200201000-00044
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinization of Intracuff Lidocaine Improves Endotracheal Tube-Induced Emergence Phenomena

Abstract: Use of 40 mg of alkalinized lidocaine, rather than lidocaine or air, to fill the endotracheal tube cuff reduces the incidence of sore throat in the postoperative period. This approach also decreases hemodynamic effects, restlessness, dysphonia, and hoarseness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 10 publications
3
73
0
2
Order By: Relevance
“…Considering the lack of similar studies in pediatric surgeries, the present study warrants further investigation of possible ways to provide smooth emergence from anesthesia in this group of patients. Warming and alkalization are two methods for increasing the diffusion rate of lidocaine and have been reported to further increase the beneficial effects of the drug [2,5,[12][13][14]. It would be interesting to try either or both of these methods in a population similar to ours and see whether they enhance the efficiency of intra-cuff lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the lack of similar studies in pediatric surgeries, the present study warrants further investigation of possible ways to provide smooth emergence from anesthesia in this group of patients. Warming and alkalization are two methods for increasing the diffusion rate of lidocaine and have been reported to further increase the beneficial effects of the drug [2,5,[12][13][14]. It would be interesting to try either or both of these methods in a population similar to ours and see whether they enhance the efficiency of intra-cuff lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that L-HCl injected alone had a slow diffusion rate across the ETT cuff (1% of release during the 6-hour period) (11). For a clinical effect, large doses of L-HCl (200 to 500 mg) were believed to be required (5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…The use of alkalinized local anesthetics into the ETT cuff offers the advantages of minimal stress response to smooth tracheal extubation and cough-free emergence. We previously reported that alkalinization of L-HCl allowed the diffusion of 65% of the neutral base form of L-HCl through the hydrophobic structure of the PVC cuff within a 6-hour period and showed that the use of a small dose (40 mg) of alkalinized L-HCl markedly improved ETT tolerance during the first postoperative day (11,12). It appears that only the hydrophobic neutral form of L-HCl was able to diffuse across a membrane, while for charged alkalinized L-HCl only a permeation phenomenon occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations